Base oil hydrotreating catalyst and method of use
By using a hydrotreating catalyst containing the base extrudate of HNPV ASA1 and ASA2, the hydrotreating of the hydrocarbon feed is solved, and the problem of difficulty in meeting the base oil product specifications and high yields in the prior art is achieved, and the effect of reducing aromatic hydrocarbon content and improving yields is achieved.
Patent Information
- Application Number
- CN202280098028.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2022-06-28
- Publication Date
- 2025-03-04
AI Technical Summary
The existing hydroisomerization catalytic dewaxing process is difficult to meet the relevant specifications and high yield requirements of base oil products at the same time, and the residual organic sulfur, nitrogen and aromatic hydrocarbons in the upstream process affect the downstream process and the final product quality.
A base oil product with reduced aromatic hydrocarbon content is prepared by hydrotreating the hydrocarbon feed using a hydrotreated catalyst containing a base extrudate formed by high nanopore volume amorphous silica-alumina (HNPV ASA1) and a second amorphous silica-alumina (ASA2).
The aromatic saturation conversion rate of base oil products is improved, the aromatic content of base oil products is significantly reduced, the product quality is improved, and the product yield is maintained.
Smart Images

Figure BDA0005234525900000111 
Figure BDA0005234525900000141 
Figure BDA0005234525900000181
Abstract
Description
Technical Field
[0001] A hydrotreating catalyst and process for producing a base oil from a hydrocarbon feedstock using a catalyst comprising a base extrudate comprising high nanopore volume amorphous silica-alumina and amorphous silica-alumina. Background Art
[0002] The hydroisomerization catalytic dewaxing process for producing base oil from hydrocarbon feedstock involves introducing feedstock into a reactor containing a dewaxing catalyst system in the presence of hydrogen. In the reactor, the feed is contacted with a hydroisomerization catalyst under hydroisomerization dewaxing conditions to provide an isomerization stream. Hydroisomerization removes aromatics and residual nitrogen and sulphur and isomerizes normal paraffins to improve cold flow properties. The isomerization stream can be further processed by contacting a hydrotreating and / or hydrofining catalyst with the stream to reduce or remove any aromatics and olefins, and to improve the color and / or other characteristics of the base oil product. Hydrotreating and / or hydrofining catalysts may include a carrier material and a noble metal, typically a combination of palladium or platinum and palladium.
[0003] Dewaxing of straight chain paraffins involves various hydroconversion reactions, including hydroisomerization, redistribution of branched chains, and secondary hydroisomerization. Continuous hydroisomerization reactions result in an increase in the degree of branching accompanied by redistribution of branched chains. Increased branching generally increases the likelihood of chain cracking, leading to increased fuel yield and base oil / lubricant yield loss. Therefore, minimizing such reactions (including the formation of hydroisomerization transition substances) can result in increased base oil / lubricant yield.
[0004] Typical challenges faced by a typical hydroisomerization catalytic dewaxing process include, among other things, providing a product that meets one or more product-related product specifications, such as cloud point, pour point, viscosity and / or viscosity index limits, while also maintaining a good product yield. In addition, further upgrading can be used, for example, during hydrotreating / hydrofining to further improve product quality, such as by saturating aromatics to reduce aromatic content to improve color and oxidative stability. However, the presence of residual organic sulfur, nitrogen and aromatics from upstream hydrotreating and hydrocracking processes can have a significant impact on downstream processes and final base oil product quality.
[0005] Therefore, there is a need for more robust catalysts for base oil / lubricant production that provide good base oil / lubricant yields while also providing improved end product properties, such as, for example, reduced product aromatics content. Summary of the invention
[0006] The present invention relates to a hydrotreating catalyst and process for converting a waxy hydrocarbon feedstock into a high-grade product, including a base oil or lubricant oil, typically having a reduced aromatic content. Such a process employs a catalyst system comprising a base extrudate formed from a mixture of a first amorphous silica-alumina (ASA1) and a second amorphous silica-alumina (ASA2) that is a high nanopore volume (HNPV) amorphous silica-alumina. It has been found that a catalyst formed from a base extrudate of a HNPV ASA (ASA1) and an amorphous silica-alumina (ASA2) advantageously provides a base oil product having a reduced base oil / lubricant product aromatic content compared to base oil products produced using other catalysts.
[0007] In one aspect, the present invention relates to a hydrotreating catalyst and process that can be used to prepare a dewaxed product comprising a base oil, particularly a base oil product of one or more product grades, by hydrotreating a suitable hydrocarbon feed stream. Although not necessarily limited thereto, one of the objects of the present invention is to provide a base oil product having a reduced aromatic content while also providing good product yields.
[0008] The catalyst generally comprises a base extrudate, the base extrudate comprising a first amorphous silica-alumina (ASA1) and a second amorphous silica-alumina (ASA2). Amorphous silica-alumina ASA1 is a high nanopore volume (HNPV) support material based on a pore volume within a defined pore size range. Amorphous silica-alumina ASA1 is characterized by having a pore volume of 0.2cc / g to 1.0cc / g within a pore size range of 11nm to 20nm. The second amorphous silica-alumina ASA2 can also be a HNPV ASA, or can also be a non-HNPV ASA, or a combination thereof. Amorphous silica-alumina ASA2 is characterized by having a pore volume of 0.02cc / g to 0.2cc / g within a pore size range of 11nm to 20nm. The base extrudates comprising ASA1 and ASA2 amorphous silica-alumina have a total pore volume of 0.12 cc / g to 1.80 cc / g in the pore size range of 2 nm to 50 nm. The catalyst further comprises at least one modifier selected from Groups 6 to 10 and 14 of the periodic table.
[0009] The use of a catalyst in a hydrotreating process generally includes contacting a hydrocarbon feed with a hydrotreating catalyst under hydrotreating conditions to produce a product or product stream. The hydrotreating catalyst comprises a base extrudate comprising an HNPV amorphous silica-alumina (ASA1) and a second amorphous silica-alumina (ASA2). The amorphous silica-alumina ASA1 has a pore volume of 0.2cc / g to 1.0cc / g in a pore size range of 11nm to 20nm, and the second amorphous silica-alumina ASA2 has a pore volume of 0.02cc / g to 0.2cc / g in a pore size range of 11nm to 20nm. The base extrudate has a total pore volume of 0.12cc / g to 1.80cc / g in a pore size range of 2nm to 50nm. The catalyst comprises at least one modifier selected from Groups 6 to 10 and Group 14 of the periodic table. DETAILED DESCRIPTION
[0010] Although illustrative embodiments of one or more aspects are provided herein, the disclosed processes may be implemented using any number of techniques. The present disclosure is not limited to the exemplary or specific embodiments, drawings, and techniques illustrated herein (including any exemplary designs and embodiments illustrated and described herein), and may be modified within the scope of the appended claims and the full scope of their equivalents.
[0011] Unless otherwise indicated, the following terms, terms and definitions apply to the present disclosure. If a term is used in the present disclosure but is not specifically defined herein, the definition from the IUPAC Compendium of Chemical Terminology, 2nd Edition (1997) may be applied, provided that the definition does not conflict with any other disclosure or definition applied herein, or does not make any claim to which the definition is applied unclear or unfeasible. If any definition or usage provided by any document incorporated herein by reference conflicts with the definition or usage provided herein, it should be understood that the definition or usage provided herein applies.
[0012] "API Gravity" means the gravity of a petroleum feed or product relative to water as determined by ASTM D4052-11.
[0013] "Viscosity Index" (VI) indicates the temperature dependence of a lubricant as determined by ASTM D2270-10 (E2011).
[0014] "Vacuum gas oil" (VGO) is a byproduct of vacuum distillation of crude oil, which can be sent to a hydrotreating unit or aromatic extraction to upgrade to base oil. VGO generally includes hydrocarbons with a boiling range distribution between 343°C (649°F) and 593°C (1100°F) at 0.101 MPa.
[0015] When used in connection with an oil feedstock, "treat," "treated," "upgrade," "upgrading," and "upgraded" describe a feedstock that is or has been subjected to hydroprocessing, or a resulting material or crude product that has a reduction in feedstock molecular weight, a reduction in feedstock boiling point range, a reduction in asphaltene concentration, a reduction in hydrocarbon radical concentration, and / or a reduction in the amount of impurities (such as sulfur, nitrogen, oxygen, halides, and metals).
[0016] "Hydroprocessing" refers to a process in which a carbonaceous feedstock is contacted with hydrogen and a catalyst at elevated temperature and pressure to achieve the purpose of removing undesirable impurities and / or converting the feedstock into desired products. Examples of hydroprocessing processes include hydrocracking, hydrotreating, catalytic dewaxing, and hydrofinishing.
[0017] "Hydrocracking" refers to a process in which hydrogenation and dehydrogenation are accompanied by cracking / fragmentation of hydrocarbons, e.g., converting heavier hydrocarbons to lighter hydrocarbons, or converting aromatics and / or cycloparaffins (cycloparaffins) to non-cyclic branched paraffins.
[0018] "Hydrotreating" refers to a process in which a sulfur- and / or nitrogen-containing hydrocarbon feed is converted into a hydrocarbon product having a reduced sulfur and / or nitrogen content (typically in combination with hydrocracking) and (correspondingly) generates hydrogen sulfide and / or ammonia as a byproduct. Such processes or steps performed in the presence of hydrogen include hydrodesulfurization, hydrodenitrogenation, hydrodemetallization and / or hydrodearomatization of hydrocarbon feed components (e.g., impurities) and / or hydrogenation of unsaturated compounds in the feedstock. Depending on the type and reaction conditions of the hydrotreating, the product of the hydrotreating process may have, for example, improved viscosity, viscosity index, saturate content, low temperature properties, volatility and depolarization. The terms "guard layer" and "guard bed" may be used synonymously and interchangeably herein to refer to a hydrotreating catalyst or a hydrotreating catalyst layer. The guard layer may be a component of a catalyst system for hydrocarbon dewaxing and may be disposed upstream of at least one hydroisomerization catalyst.
[0019] "Catalytic dewaxing" or hydroisomerization refers to a process whereby normal paraffins are isomerized to their more branched counterparts by contact with a catalyst in the presence of hydrogen.
[0020] "Hydrofinishing" refers to a process designed to improve the oxidation stability, UV stability and appearance of the hydrofinished product by removing trace amounts of aromatics, olefins, color bodies and solvents. UV stability refers to the stability of the hydrocarbons tested when exposed to UV light and oxygen. Instability is indicated when a visible precipitate is formed, usually looking like Hoc or turbidity, or a darker color is produced after exposure to ultraviolet light and air. A general description of hydrofinishing can be found in U.S. Pat. Nos. 3,852,207 and 4,673,487.
[0021] The term "hydrogen" or "hydrogen" refers to hydrogen itself, and / or one or more compounds that provide a source of hydrogen.
[0022] "BET surface area" is determined from the amount of N2 adsorption at boiling temperature. The BET surface area is calculated by a 5-point method at P / P0 = 0.050, 0.088, 0.125, 0.163 and 0.200. The sample is first pretreated at 400°C for 6 hours in the presence of flowing dry N2 to eliminate any adsorbed volatiles, such as water or organic matter.
[0023] "Cut point" refers to the temperature at which a predetermined degree of separation is achieved on the true boiling point (TBP) curve.
[0024] "Pour point" refers to the temperature at which an oil begins to flow under controlled conditions. Pour point can be determined, for example, by ASTM D5950.
[0025] "Cloud point" refers to the temperature at which a sample of a lubricating base oil begins to develop turbidity when the oil is cooled under specified conditions. The cloud point of a lubricating base oil is complementary to its pour point. The cloud point can be determined, for example, by ASTM D5773.
[0026] "Nanopore diameter" and "nanopore volume" are determined by N2 adsorption at boiling temperature and calculated from the N2 isotherm by the BJH method described in EPBarrett, LGJoyner and PPHalenda, "The determination of pore volume and area distributions in porous substances. I. Computations from nitrogen isotherms." J.Am.Chem.Soc.73,373–380,1951. The samples were first pretreated at 400°C for 6 hours in the presence of flowing dry N2 to eliminate any adsorbed volatiles, such as water or organic matter. The pore diameters at 10%, 50% and 90% of the total nanopore volume are referred to as d 10 d 50and d 90 , can also be determined from such N2 adsorption measurements.
[0027] "TBP" refers to the boiling point of a hydrocarbonaceous feed or product as determined by simulated distillation (SimDist) by ASTM D2887-13.
[0028] "Hydrocarbon-containing," "hydrocarbons," and similar terms refer to compounds containing only carbon and hydrogen atoms. Other identifiers may be used to indicate the presence of specific groups, if any, in a hydrocarbon (e.g., a halogenated hydrocarbon indicates the presence of one or more halogen atoms replacing the equivalent amount of hydrogen atoms in the hydrocarbon).
[0029] The term "periodic table" refers to the version of the IUPAC Periodic Table of the Elements as of June 22, 2007, and the numbering scheme for the groups of the periodic table is as described in Chem. Eng. News, 63 (5), 26-27 (1985). "Group 2" refers to IUPAC Group 2 elements, such as magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), and combinations thereof, in elemental form, compound form, or ionic form. "Group 6" refers to IUPAC Group 6 elements, such as chromium (Cr), molybdenum (Mo), and tungsten (W). "Group 7" refers to IUPAC Group 7 elements, such as manganese (Mn), rhenium (Re), and combinations thereof, in elemental form, compound form, or ionic form. "Group 8" refers to IUPAC Group 8 elements, such as iron (Fe), ruthenium (Ru), osmium (Os), and combinations thereof, in elemental form, compound form, or ionic form. "Group 9" refers to IUPAC Group 9 elements, such as cobalt (Co), rhodium (Rh), iridium (Ir), and combinations thereof, in either elemental form, compound form, or ionic form. "Group 10" refers to IUPAC Group 10 elements, such as nickel (Ni), palladium (Pd), platinum (Pt), and combinations thereof, in either elemental form, compound form, or ionic form. "Group 14" refers to IUPAC Group 14 elements, such as germanium (Ge), tin (Sn), lead (Pb), and combinations thereof, in either elemental form, compound form, or ionic form.
[0030] The term "support", particularly as used in the term "catalyst support", refers to a conventional material, usually solid, having a high surface area, to which the catalyst material is attached. The support material may be inert or participate in the catalytic reaction and may be porous or non-porous. Typical catalyst supports include various carbons, aluminas, silicas and silica-aluminas, such as amorphous aluminosilicates, zeolites, alumina-boria, silica-alumina-magnesia, silica-alumina-titania and materials obtained by adding other zeolites and other composite oxides to the aforementioned materials.
[0031] "Molecular sieve" refers to a material having pores of uniform molecular size within a framework structure, such that, depending on the type of molecular sieve, only certain molecules can enter the pore structure of the molecular sieve, while other molecules are excluded, for example, due to molecular size and / or reactivity. The terms "molecular sieve" and "zeolite" are synonymous and include (a) intermediates and (b) final or target molecular sieves and molecular sieves produced by (1) direct synthesis or (2) post-crystallization treatment (secondary modification). Secondary synthesis techniques allow the synthesis of target materials from intermediate materials by heteroatom lattice substitution or other techniques. For example, aluminosilicates can be synthesized from intermediate borosilicates by post-crystallization heteroatom lattice substitution of Al for B. Such techniques are known, for example, as described in U.S. Patent No. 6,790,433. Zeolites, crystalline aluminum phosphates, and crystalline silicoaluminophosphates are representative examples of molecular sieves.
[0032] In the present disclosure, although compositions and methods or processes are often described as "comprising" various components or steps, unless otherwise specified, the compositions and methods may also "consist essentially of" or "consist of" the various components or steps.
[0033] The terms "a", "an", and "the" are intended to include plural alternatives, such as at least one. For example, unless otherwise indicated, disclosure of "a transition metal" or "an alkali metal" is intended to encompass one transition metal or alkali metal, or a mixture or combination of more than one transition metal or alkali metal.
[0034] All numerical values in the detailed description and claims herein are modified by the indicated value of "about" or "approximately", and take into account experimental error and variations that would be expected by a person of ordinary skill in the art.
[0035] In one aspect, the present invention is a hydroprocessing catalyst useful for preparing a dewaxed product comprising a base oil / lubricant having a reduced aromatic content, the catalyst comprising a base extrudate formed of a high nanopore volume (HNPV) amorphous silica-alumina (ASA1) and a second amorphous silica-alumina; wherein the amorphous silica-alumina ASA1 has a pore volume of 0.2 cc / g to 1.0 cc / g in the pore size range of 11 nm to 20 nm, and the second amorphous silica-alumina ASA2 has a pore volume of 0.02 cc / g to 0.2 cc / g in the pore size range of 11 nm to 20 nm. The base extrudate has a total pore volume of 0.12 cc / g to 1.80 cc / g in the pore size range of 2 nm to 50 nm. The catalyst comprises at least one modifier selected from Groups 6 to 10 and Group 14 of the periodic table.
[0036] In another aspect, the present invention is a hydroprocessing catalyst useful for preparing a dewaxed product comprising a base oil / lubricant having a reduced aromatic content, the catalyst comprising a base extrudate formed of a high nanopore volume (HNPV) amorphous silica-alumina (ASA1) and a second amorphous silica-alumina (ASA2); wherein the HNPV ASA1 amorphous silica-alumina has a pore volume of 0.2 cc / g to 1.0 cc / g in a pore size range of 11 nm to 20 nm, and the second amorphous silica-alumina ASA2 has a pore volume of 0.02 cc / g to 0.2 cc / g in a pore size range of 11 nm to 20 nm. The base extrudate has a total pore volume of 0.12 cc / g to 1.80 cc / g in a pore size range of 2 nm to 50 nm. The catalyst comprises at least one modifier selected from Groups 6 to 10 and 14 of the periodic table.
[0037] In a further aspect, the present invention relates to a hydrotreating process useful for preparing a dewaxed product comprising a base oil having a reduced aromatic content, the process comprising contacting a hydrocarbon feed with a hydrotreating catalyst under hydrotreating conditions to produce a product or product stream; wherein the hydrotreating catalyst comprises a base extrudate formed of a high nanopore volume (HNPV) amorphous silica-alumina (ASA1) and a second amorphous silica-alumina (ASA2); wherein the HNPV ASA1 has a pore volume of 0.2 cc / g to 1.0 cc / g in the pore size range of 11 nm to 20 nm, and the second amorphous silica-alumina ASA2 has a pore volume of 0.02 cc / g to 0.2 cc / g in the pore size range of 11 nm to 20 nm. The base extrudate has a total pore volume of 0.12 cc / g to 1.80 cc / g in the pore size range of 2 nm to 50 nm. The catalyst comprises at least one modifier selected from Groups 6 to 10 and Group 14 of the Periodic Table.
[0038] The first amorphous silica-alumina (ASAl) used in hydrotreating catalysts and processes is often referred to as "high nanopore volume" amorphous silica-alumina (ASA), abbreviated herein as "HNPV" amorphous silica-alumina or "HNPV" ASA1. HNPV ASA1 can be conveniently characterized according to its pore volume within an average pore size range. The term "nanopore volume", abbreviated herein as "NPV", provides a convenient label to define the pore volume ranges of ASA1 and the values within those ranges, such as the NPV pore volume in the pore size range of 2nm to 6nm, the pore size range of 6-11nm, the pore size range of 11-20nm, and the pore size range of 20nm to 50nm. Generally, the HNPV ASA1 has a pore volume of 0.2cc / g to 1.0cc / g in the pore size range of 11nm to 20nm, or more specifically, a pore volume of 0.24cc / g to 0.85cc / g in the pore size range of 11nm to 20nm, or a pore volume of 0.28cc / g to 0.7cc / g in the pore size range of 11nm to 20nm. Independently, or in addition to the aforementioned 11nm to 20nm range, the first amorphous silica-alumina ASA1 has a pore volume of 0.05cc / g to 1.0cc / g in the pore size range of 2nm to 6nm, or a pore volume of 0.06cc / g to 0.8cc / g in the pore size range of 2nm to 6nm, or a pore volume of 0.07cc / g to 0.6cc / g in the pore size range of 2nm to 6nm. Independently, or in addition to the aforementioned 2nm to 6nm and 11nm to 20nm ranges, ASA1 may have a pore volume of 0.05cc / g to 1.0cc / g in the pore diameter range of 6nm to 11nm, or a pore volume of 0.06cc / g to 0.8cc / g in the pore diameter range of 6nm to 11nm, or a pore volume of 0.07cc / g to 0.6cc / g in the pore diameter range of 6nm to 11nm. Independently, or in addition to the aforementioned 2nm to 6nm, 6nm to 11nm, and 11nm to 20nm ranges, ASA1 may have a pore volume of 0.05cc / g to 1.0cc / g in the pore diameter range of 20nm to 50nm, or a pore volume of 0.07cc / g to 0.8cc / g in the pore diameter range of 20nm to 50nm, or a pore volume of 0.09cc / g to 0.6cc / g in the pore diameter range of 20nm to 50nm.
[0039] HNPV ASA1 can also be characterized by its total pore volume over a range of pore sizes. For example, in addition to the aforementioned NPV pore volume, or separately and independently, HNPV ASA1 can have a total pore volume of 0.3cc / g to 2.0cc / g over a pore size range of 2nm to 50nm, or a total pore volume of 0.5cc / g to 1.9cc / g over a pore size range of 2nm to 50nm, or a total pore volume of 0.7cc / g to 1.8cc / g over a pore size range of 2nm to 50nm.
[0040] In contrast, the pore size distribution of non-HNPV amorphous silica-alumina is generally biased towards a larger pore volume content in a smaller pore size range. For example, such non-HNPV ASAs generally have a pore volume of less than about 0.2cc / g, or less than about 0.18cc / g in the pore size range of 11nm to 20nm, and / or a pore volume of less than about 0.15cc / g, or less than about 0.1cc / g in the pore size range of 20nm to 50nm.
[0041] The second amorphous silica-alumina ASA2 used in the hydrotreating catalyst and process can be conveniently characterized according to its pore volume within an average pore size range. The term "nanopore volume", abbreviated herein as "NPV", provides a convenient label to define the pore volume ranges of the amorphous silica-alumina ASA2 and the values within those ranges, such as the NPV pore volume in the pore size range of 2nm to 6nm, the pore size range of 6nm to 11nm, the pore size range of 11nm to 20nm, and the pore size range of 20nm to 50nm. Generally speaking, the amorphous silica-alumina ASA2 has a pore volume of 0.02cc / g to 0.2cc / g in the pore size range of 11nm to 20nm, or more specifically, a pore volume of 0.03cc / g to 0.18cc / g in the pore size range of 11nm to 20nm, or a pore volume of 0.04cc / g to 0.16cc / g in the pore size range of 11nm to 20nm. Independently, or in addition to the aforementioned 11 nm to 20 nm range, the amorphous silica-alumina ASA2 may have a pore volume of 0.05 cc / g to 1.0 cc / g in the pore diameter range of 2 nm to 6 nm, or a pore volume of 0.06 cc / g to 0.9 cc / g in the pore diameter range of 2 nm to 6 nm, or a pore volume of 0.07 cc / g to 0.8 cc / g in the pore diameter range of 2 nm to 6 nm. Independently, or in addition to the aforementioned 2 nm to 6 nm and 11 nm to 20 nm ranges, the amorphous silica-alumina ASA2 may have a pore volume of 0.05 cc / g to 1.0 cc / g in the pore diameter range of 6 nm to 11 nm, or a pore volume of 0.06 cc / g to 0.8 cc / g in the pore diameter range of 6 nm to 11 nm, or a pore volume of 0.07 cc / g to 0.6 cc / g in the pore diameter range of 6 nm to 11 nm. Independently, or in addition to the aforementioned 2nm to 6nm, 6nm to 11nm, and 11nm to 20nm ranges, the amorphous silica-alumina ASA2 may have a pore volume of 0.01cc / g to 0.2cc / g in the pore diameter range of 20nm to 50nm, or a pore volume of 0.015cc / g to 0.15cc / g in the pore diameter range of 20nm to 50nm, or a pore volume of 0.02cc / g to 0.1cc / g in the pore diameter range of 20nm to 50nm.
[0042] The second amorphous silica-alumina ASA2 can also be characterized by its total pore volume within the pore size range. For example, in addition to the aforementioned NPV pore volume, or separately and independently, the amorphous silica-alumina ASA2 can have a total pore volume of 0.3cc / g to 2.0cc / g within the pore size range of 2nm to 50nm, or a total pore volume of 0.4cc / g to 1.8cc / g within the pore size range of 2nm to 50nm, or a total pore volume of 0.5cc / g to 1.6cc / g within the pore size range of 2nm to 50nm.
[0043] The pore size distribution of suitable non-HNPV ASAs is generally biased towards a larger pore volume content in a smaller pore size range. For example, such non-HNPV ASAs generally have a pore volume of less than about 0.2cc / g, or less than about 0.18cc / g in the pore size range of 11nm to 20nm, and / or a pore volume of less than about 0.15cc / g, or less than about 0.1cc / g in the pore size range of 20nm to 50nm.
[0044] HNPV amorphous silica-alumina ASA1 and second amorphous silica-alumina ASA2 can be commercially available materials from Sasol, JGC Catalysts and Chemicals, and PIDC (Pacific Industrial Development Corporation). Suitable HNPV ASAs and non-HNPV ASAs are commercially available and are known in the patent literature, including, for example, in US 10,183,282. One such ASA family includes, for example, Sasol's ASA (Table 1).
[0045] Table 1
[0046]
[0047] *After activation at 550°C for 3 hours
[0048] The first amorphous silica-alumina and the second amorphous silica-alumina typically have different silica contents. For example, the silica content of the first amorphous silica-alumina can be in the range of 0.5 wt % to 15 wt %, or 1 wt % to 10 wt %, or 1.5 wt % to 8 wt %. The silica content of the second amorphous silica-alumina can be in the range of 15 wt % to 90 wt %, or 20 wt % to 85 wt %, or 25 wt % to 80 wt %.
[0049] The relative amounts of each of the first and second ASAs in the base extrudate may also vary, typically within a ratio range of 4: 1 to 1: 4. In some cases, narrower ranges may be appropriate, for example, a ratio of ASA1 to ASA2 of 4: 1 to 1: 2, or 4: 1 to 1: 1, or 4: 1 to 2: 1, or 2: 1 to 1: 4, or 2: 1 to 1: 2, or 2: 1 to 1: 1, 1: 2 to 1: 1, or 1: 4 to 1: 2, or 1: 4 to 1: 1. Generally, the total amount of the first amorphous silica-alumina and the second amorphous silica-alumina in the base extrudate is within a range of 10 wt % to 95 wt %, or 20 wt % to 90 wt %, or 25 wt % to 85 wt %.
[0050] The catalyst comprising the base extrudate formed by HNPV ASA1 and the second amorphous silica-alumina ASA2 generally also comprises at least one modifier selected from Group 6 to Group 10 and Group 14 of the Periodic Table (IUPAC). Suitable Group 6 modifiers include Group 6 elements, such as chromium (Cr), molybdenum (Mo) and tungsten (W) in any of elemental form, compound form or ionic form, and combinations thereof. Suitable Group 7 modifiers include Group 7 elements, such as manganese (Mn), rhenium (Re) and combinations thereof in any of elemental form, compound form or ionic form. Suitable Group 8 modifiers include Group 8 elements, such as ruthenium (Ru), osmium (Os) and combinations thereof in any of elemental form, compound form or ionic form. Suitable Group 9 modifiers include Group 9 elements, such as cobalt (Co), rhodium (Rh), iridium (Ir) and combinations thereof in any of elemental form, compound form or ionic form. Suitable Group 10 modifiers include Group 10 elements, such as nickel (Ni), palladium (Pd), platinum (Pt), and combinations thereof, in elemental, compound, or ionic form. Suitable Group 14 modifiers include Group 14 elements, such as germanium (Ge), tin (Sn), lead (Pb), and combinations thereof, in elemental, compound, or ionic form. In addition, optional Group 2 modifiers may be present, including Group 2 elements, such as magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), and combinations thereof, in elemental, compound, or ionic form.
[0051] Modifiers advantageously include one or more Group 10 metals. Group 10 metals may be, for example, platinum, palladium or a combination thereof. In some respects, platinum is a suitable Group 10 metal, together with another Group 6 to 10 and Group 14 metals. Although not limited thereto, Group 6 to 10 and Group 14 metals may be more narrowly selected from Pt, Pd, Ni, Re, Ru, Ir, Sn or a combination thereof. Combined with Pt as the first metal in the catalyst, the optional second metal in the catalyst may also be more narrowly selected from Pd, Ni, Re, Ru, Ir, Sn or a combination thereof in Group 6 to 10 and Group 14 metals. In more specific cases, the catalyst may include Pt as Group 10 metal in an amount of 0.01 wt % to 5.0 wt %, or 0.01 wt % to 2.0 wt %, or 0.1 wt % to 2.0 wt %, more specifically 0.01 wt % to 1.0 wt %, or 0.3 wt % to 0.8 wt %. An optional second metal may be present as a Group 6 to 10 and Group 14 metal selected from Pd, Ni, Re, Ru, Ir, Sn or a combination thereof in an amount of 0.01 wt % to 5.0 wt %, or 0.01 wt % to 2.0 wt %, or 0.1 wt % to 2.0 wt %, more specifically 0.01 wt % to 1.0 wt % and 0.01 wt % to 1.5 wt %.
[0052] The metal content in the catalyst can vary within a useful range, for example, the total modified metal content of the catalyst can be 0.01 wt % to 5.0 wt %, or 0.01 wt % to 2.0 wt %, or 0.1 wt % to 2.0 wt % (based on the total weight of the catalyst). In some cases, the catalyst comprises 0.1 wt % to 2.0 wt % of Pt as one of the modified metals and 0.01 wt % to 1.5 wt % of a second metal selected from Groups 6 to 10 and Group 14, or 0.3 wt % to 1.0 wt % of Pt and 0.03 wt % to 1.0 wt % of a second metal, or 0.3 wt % to 1.0 wt % of Pt and 0.03 wt % to 0.8 wt % of a second metal. In some cases, the ratio of the first Group 10 metal to the optional second metal selected from Groups 6 to 10 and 14 can range from 5:1 to 1:5, or 3:1 to 1:3, or 1:1 to 1:2, or 5:1 to 2:1, or 5:1 to 3:1, or 1:1 to 1:3, or 1:1 to 1:4.
[0053] The catalyst may further comprise an additional matrix material selected from alumina, silica, ceria, titania, tungsten oxide, zirconium oxide or a combination thereof. In a more specific case, the first catalyst comprises 0.01 wt % to 5.0 wt % of a modified metal, 1 wt % to 99 wt % of a matrix material and 0.1 wt % to 99 wt % of a base extrudate comprising HNPV ASA1 and ASA2. The catalyst may also be described more narrowly, for example, the catalyst may comprise 0.01 wt % to 5.0 wt % of a modifier, 15 wt % to 85 wt % of a matrix material and 15 wt % to 85 wt % of a HNPV ASA1 and ASA2 base extrudate. More than one matrix material may be used, for example, the matrix material may comprise about 15 wt % to 65 wt % of a first matrix material and about 15 wt % to 65 wt % of a second matrix material. In such cases, the first matrix material and the second matrix material are generally different in one or more features (such as material type or pore volume and pore distribution features). Where one or more matrix materials are used, the first, second (and any additional) matrix materials may also be of the same type of matrix material, for example, the matrix material may comprise one or more aluminum oxides.
[0054] Suitable HNPV and non-HNPV aluminas are commercially available and are known in the patent literature, including, for example, in US 10,183,282. One such family of aluminas includes, for example, Sasol's Alumina (Table 2). Sasol Alumina may also be suitable.
[0055] Table 2
[0056]
[0057] *After activation at 550°C for 3 hours
[0058] The catalyst base extrudate is also suitably characterized by pore volume, both total pore volume and pore volume in certain average pore size ranges. As with the HNPV ASA1 and ASA2 components, the base extrudate can be characterized by pore volume in a pore size range of 2nm to 6nm, a pore size range of 6nm to 11nm, a pore size range of 11nm to 20nm, and a pore size range of 20nm to 50nm. Generally, the base extrudate has a total pore volume of 0.12cc / g to 1.80cc / g in a pore size range of 2nm to 50nm, or more particularly, a total pore volume of 0.20cc / g to 1.65cc / g in a pore size range of 2nm to 50nm, or a total pore volume of 0.25cc / g to 1.50cc / g in a pore size range of 2nm to 50nm.
[0059] Independently, or in addition to the aforementioned total pore volume 2nm to 50nm range, the base extrudate may have a pore volume of 0.05cc / g to 0.8cc / g in the pore diameter range of 2nm to 6nm, or a pore volume of 0.08cc / g to 0.6cc / g in the pore diameter range of 2nm to 6nm, or a pore volume of 0.1cc / g to 0.5cc / g in the pore diameter range of 2nm to 6nm. Independently, or in addition to the aforementioned pore volume of 2nm to 6nm and 2nm to 50nm, the base extrudate may have a pore volume of 0.05cc / g to 1.0cc / g in the pore diameter range of 6nm to 11nm, or a pore volume of 0.08cc / g to 0.9cc / g in the pore diameter range of 6nm to 11nm, or a pore volume of 0.1cc / g to 0.8cc / g in the pore diameter range of 6nm to 11nm. Independently, or in addition to the foregoing 2 nm to 6 nm pore volume, 6 nm to 11 nm pore volume, and 2 nm to 50 nm total pore volume ranges, the base extrudate can have a pore volume of 0.02 cc / g to 0.3 cc / g in the pore diameter range of 11 nm to 20 nm, or a pore volume of 0.03 cc / g to 0.25 cc / g in the pore diameter range of 11 nm to 20 nm, or a pore volume of 0.04 cc / g to 0.2 cc / g in the pore diameter range of 11 nm to 20 nm. Independently, or in addition to the foregoing 2nm to 6nm pore volume, 6nm to 11nm pore volume, 11nm to 20nm pore volume, and 2nm to 50nm total pore volume ranges, the base extrudate can have a pore volume of 0.01cc / g to 0.3cc / g in the pore diameter range of 20nm to 50nm, or a pore volume of 0.012cc / g to 0.25cc / g in the pore diameter range of 20nm to 50nm, or a pore volume of 0.015cc / g to 0.2cc / g in the pore diameter range of 20nm to 50nm.
[0060] The base extrudate can be prepared according to any suitable method. For example, the base extrudate can be conveniently prepared by mixing the components together and extruding the fully mixed HNPV ASA1 and ASA2 components to form the base extrudate. Next, the extrudate is dried and calcined, and any modifier is subsequently loaded onto the base extrudate. The modifier can be dispersed onto the base extrudate using a suitable impregnation technique. However, the method for making the base extrudate is not intended to be particularly limited according to specific process conditions or techniques.
[0061] The hydrocarbon feedstock may generally be selected from a variety of base oil feedstocks, and advantageously includes gas oils; vacuum gas oils; long boiling residues; vacuum residues; atmospheric distillates; heavy fuels; oils; waxes and paraffins; used oils; deasphalted residues or crude oils; charges resulting from thermal or catalytic conversion processes; shale oils; cycle oils; fats, oils and waxes of animal and vegetable origin; petroleum and slack waxes; or combinations thereof. The hydrocarbon feed may also comprise a feed hydrocarbon cut in a distillation range of 400°F to 1300°F, or 500°F to 1100°F, or 600°F to 1050°F, and / or wherein the hydrocarbon feed has a KV100 (kinematic viscosity at 100°C) range of about 3 cSt to 30 cSt or about 3.5 cSt to 15 cSt.
[0062] The hydrocarbon feed can be subjected to an initial hydrotreating step before receiving the hydrotreating process of the present invention. Although not limited to or required, such initial hydrotreating step can include hydrodesulfurization, hydrodenitrogenation, hydrodemetallization and / or hydrodearomatization of components (e.g., impurities) of the hydrocarbon feed. The hydrocarbon feed can also be subjected to initial hydrotreating to improve certain properties of the hydrocarbon feed, such as, for example, viscosity properties. In some cases, the hydrotreating process can be advantageously used in combination with (e.g., used thereafter) a hydroisomerization process of a light or heavy neutral base oil feedstock (such as vacuum gas oil (VGO)). The hydrotreating process can then be implemented after this initial hydrotreating by contacting the hydrocarbon feed with a catalyst formed by an ASA1 / ASA2 base extrudate.
[0063] One or more products or product streams may be used to produce one or more base oil products, such as multiple grades having a KV100 in the range of about 2 cSt to 30 cSt. In some cases, such base oil products may have a pour point of no more than about -5°C, or -12°C, or -14°C.
[0064] The processes and systems may also be combined with additional process steps or system components, for example, a hydrotreating catalyst may be used to further subject the feedstock to other hydrotreating conditions prior to contacting the hydrocarbon feed with the hydrotreating catalyst. Additional optional layered catalysts may also be used, for example, where the hydrotreating catalyst comprises a guard layer catalyst comprising a refractory inorganic oxide material containing about 0.1 wt % to 1 wt % Pt and about 0.2 wt % to 1.5 wt % Pd.
[0065] The process and catalyst system of the present invention provide an advantage in that the use of the catalyst system of the present invention comprising HNPV ASA1 and a second amorphous silica-alumina ASA2 improves base oil product properties (e.g., reduced aromatics content) compared to the same process using a similar catalyst comprising a base extrudate that does not contain a combination of the HNPV ASA1 and ASA2 components. In some cases, when using a hydrotreating catalyst of the present invention comprising a base extrudate formed of ASA1 and ASA2 amorphous silica-alumina, the aromatics content of the base oil product is significantly reduced by at least about 0.5 wt%, or 1.0 wt%, or 1.5 wt%, or 2.0 wt% compared to the same process using a similar catalyst that does not contain the two ASAs in the base extrudate. The base oil product aromatic content may also be characterized by increased aromatic saturation conversion, wherein the base oil product aromatic saturation conversion is significantly increased by at least about 0.5 wt%, 1.0 wt%, or 1.5 wt%, or 2.0 wt% when the hydrotreating catalyst of the present invention is used as compared to a similar catalyst in the same process that does not contain both ASA1 and ASA2 in the catalyst base extrudate.
[0066] In practice, hydrodewaxing is mainly used to reduce the pour point of base oil and / or reduce the cloud point of base oil by removing wax from base oil. Typically, dewaxing uses a catalytic process to treat wax, usually before dewaxing, the dewaxing device feed is upgraded to improve the viscosity index, reduce aromatics and heteroatom content, and reduce the amount of low-boiling components in the dewaxing device feed. Some dewaxing catalysts complete the wax conversion reaction by cracking the wax molecules into molecules of lower molecular weight. Other dewaxing processes can transfer the wax contained in the hydrocarbon feed to the wax isomerization process to produce isomerized molecules with a pour point lower than that of non-isomerized molecular counterparts. As used herein, isomerization covers the hydroisomerization process using hydrogen in the isomerization of wax molecules under catalytic hydroisomerization conditions.
[0067] Suitable hydrodewaxing and / or hydrotreating conditions generally depend on the feed used, the catalyst used, the desired yield, and the desired base oil properties. Typical conditions include: 500°F to 775°F (260°C to 413°C) temperature; 15 psig to 3000 psig pressure (0.10 MPa to 20.68 MPa gauge); 0.25 hr -1 Up to 20 hours -1 LHSV; and 2000 SCF / bbl to 30,000 SCF / bbl hydrogen to feed ratio (356 to 5340 m 3 H2 / m 3Feed). Generally, hydrogen is separated from the product and recycled to the isomerization zone. The dewaxing process useful in the present invention is performed in the presence of hydrogen, and the ratio of hydrogen to hydrocarbon is generally in the range of about 2000 to about 10,000 standard cubic feet H2 / barrel of hydrocarbon, and is generally about 2500 to about 5000 standard cubic feet H2 / barrel of hydrocarbon. Such conditions may be applicable to the hydrotreating conditions of the hydrotreating zone (including, for example, a guard bed upstream of the hydroisomerization catalyst) and the hydroisomerization conditions that may be used upstream of the hydrotreating process of the present invention. Suitable dewaxing conditions and processes are described, for example, in U.S. Patent Nos. 5,135,638, 5,282,958, and 7,282,134.
[0068] Suitable catalyst systems typically include a hydrotreating catalyst as described herein, comprising a base extrudate formed by ASA1 and ASA2, arranged so that the feedstock contacts the hydrotreating catalyst. The hydrotreating process and catalyst of the present invention are generally used after the hydrodewaxing / hydroisomerization process step. The hydrotreating catalyst can be used alone, in combination with other catalysts, and / or in a layered catalyst system. Additional processing steps and catalysts can be used in conjunction with the hydrotreating process of the present invention, for example, as noted, including a hydrotreating catalyst / step, a protective layer and / or a hydrofining catalyst / step.
[0069] Example
[0070] The HNPV amorphous silica-alumina ASA1 and the second amorphous silica-alumina ASA2 used in the following examples are both provided as commercially available materials according to the foregoing description. The comparative catalysts containing only one ASA component (i.e., ASA1 or ASA2) in the base extrudate are formed by combining the corresponding ASA component with commercially available alumina. The properties of these materials used in the examples are shown in Table 3. ASA1 contains 5 wt% silica and has large pores and a high nanopore volume, while ASA2 contains 70 wt% silica and has smaller pores and a low nanopore volume.
[0071] Table 3
[0072]
[0073]
[0074] The metal dispersion of PtPd bimetallic particles was determined by hydrogen chemisorption. The measurement involved the following steps: After reduction, the sample was kept evacuated until the total H2 chemisorption was measured at 110°C at the following pressures: 20, 50, 80, 110, 140, 170, 200, 240, 280, 320, and 360 Torr. After measuring the total chemisorption, the catalyst was evacuated for 10 minutes and the isothermal H2 chemisorption was repeated to determine the weak and strong H2 chemisorption components. The metal dispersion was calculated by the strongly adsorbed hydrogen per PtPd atom.
[0075] The S / C surface to core ratio, i.e., the Pt or Pd distribution in the extrudate, was determined by measuring the Pt or Pd concentration in the cross-sectioned catalyst particles using electron probe microanalysis (EPMA). After collecting the metal spectrum, the S / C ratio was calculated by dividing the surface concentration of the measured particle of Pt or Pd by the core concentration.
[0076] Example 1 - Preparation of Hydrotreating Catalyst A
[0077] Comparative hydroprocessing catalyst A was prepared as follows: 80 wt% of amorphous silica-alumina ASA1 was composited with conventional alumina, and the mixture was extruded, dried and calcined. The dried and calcined extrudates were impregnated in a solution containing platinum and palladium. The total noble metal loading was 0.54 wt%.
[0078] Example 2 - Preparation of Hydrotreating Catalyst B
[0079] Comparative hydrotreating catalyst B was prepared as described for catalyst A, except that ASA2 was used instead of ASA1 to provide a mixture containing 80 wt% amorphous silica-alumina ASA2 and 20 wt% alumina. The dried and calcined extrudates were impregnated with platinum and palladium to provide a total precious metal loading of 0.54 wt%.
[0080] Example 3 - Preparation of Hydrotreating Catalyst C
[0081] Hydrotreating Catalyst C was prepared as described for Catalyst A, except that a 50 wt% / 50 wt% combination of ASA1 and ASA2 was used to provide a mixture containing 80 wt% amorphous silica-alumina and 20 wt% alumina. The dried and calcined extrudates were impregnated with platinum and palladium to provide a total precious metal loading of 0.54 wt%.
[0082] Catalyst properties are listed in Table 4 (relative to Base Catalyst A).
[0083] Table 4
[0084]
[0085] 1 Determination of metal dispersion by H2 chemisorption
[0086] 2,3 S / C: surface to center ratio of Pt or Pd
[0087] From Table 4, the relative metal dispersion and distribution in each catalyst can be noted. Catalyst A contains ASA1 in the base extrudate support and exhibits good metal dispersion and poor metal distribution. Catalyst B contains ASA2 in the base extrudate support and exhibits poor metal dispersion and good metal distribution. In contrast, Catalyst C uses a combination of ASA1 and ASA2 in the base extrudate support and exhibits good metal dispersion and good metal distribution.
[0088] Example 4 - Hydroprocessing Performance of Catalysts A, B and C
[0089] A dewaxed heavy neutral feedstock having the properties shown in Table 5 was hydrotreated using Catalysts A, B and C.
[0090] Table 5
[0091]
[0092]
[0093] The hydrotreating reaction was carried out in a micro-unit equipped with a downflow reactor. The run was operated at a total pressure of 2100 psig. The catalyst was activated by a standard reduction procedure before the feed was introduced. The feed was passed through the reactor at a liquid hourly space velocity (LHSV) of 1.2. The ratio of hydrogen to oil was about 3000 scfb. The hydrotreating reaction temperature was adjusted in the range of 350°F-550°F. Table 6 shows the aromatic conversion results for Catalysts A, B and C.
[0094] Table 6
[0095]
[0096] Compared to Catalyst A (having ASA A (ASA1) in the base extrudate support) and Catalyst B (having ASA2 in the base extrudate support), Catalyst C (having both ASA1 and ASA2 in the base extrudate support) had an approximately 4% improvement in aromatic saturation conversion relative to Catalyst B and a 16% improvement relative to Catalyst A.
[0097] This application should be understood to cover the full scope of the subject claims set forth in the following numbered paragraphs P1 to P30:
[0098] P1. A hydroprocessing catalyst, which can be used to prepare a hydroprocessed dewaxed product, the dewaxed product comprising a base oil having an improved aromatic saturation conversion rate, the hydroprocessing catalyst comprising
[0099] A base extrudate comprising a first amorphous silica-alumina (ASA1) and a second amorphous silica-alumina (ASA2), wherein
[0100] The first amorphous silica-alumina has a pore volume of 0.2 cc / g to 1.0 cc / g in a pore diameter range of 11 nm to 20 nm;
[0101] The second amorphous silica-alumina has a pore volume of 0.02 cc / g to 0.2 cc / g in a pore diameter range of 11 nm to 20 nm; and
[0102] The base extrudate has a total pore volume of 0.12 cc / g to 1.80 cc / g in a pore size range of 2 nm to 50 nm; and
[0103] At least one modifier selected from Groups 6 to 10 and 14 of the periodic table.
[0104] P2. The catalyst according to paragraph P1, wherein the modifier comprises a metal from Groups 8 to 10 of the Periodic Table.
[0105] P3. A catalyst according to paragraph P2, wherein the modifier is a Group 10 metal comprising Pt, Pd, or a combination thereof.
[0106] P4. A catalyst according to any one of paragraphs P1 to P3, wherein the first amorphous silica-alumina has a pore volume of 0.05cc / g to 1.0cc / g in the pore diameter range of 2nm to 6nm, or a pore volume of 0.06cc / g to 0.8cc / g in the pore diameter range of 2nm to 6nm, or a pore volume of 0.07cc / g to 0.6cc / g in the pore diameter range of 2nm to 6nm.
[0107] P5. A catalyst according to any one of paragraphs P1 to P4, wherein the first amorphous silica-alumina has a pore volume of 0.05cc / g to 1.0cc / g in the pore diameter range of 6nm to 11nm, or a pore volume of 0.06cc / g to 0.8cc / g in the pore diameter range of 6nm to 11nm, or a pore volume of 0.07cc / g to 0.6cc / g in the pore diameter range of 6nm to 11nm.
[0108] P6. A catalyst according to any of paragraphs P1 to P5, wherein the first amorphous silica-alumina has a pore volume of 0.24 cc / g to 0.85 cc / g in the pore diameter range of 11 nm to 20 nm, or a pore volume of 0.28 cc / g to 0.7 cc / g in the pore diameter range of 11 nm to 20 nm.
[0109] P7. A catalyst according to any one of paragraphs P1 to P6, wherein the first amorphous silica-alumina has a pore volume of 0.05cc / g to 1.0cc / g in a pore diameter range of 20nm to 50nm, or a pore volume of 0.07cc / g to 0.8cc / g in a pore diameter range of 20nm to 50nm, or a pore volume of 0.09cc / g to 0.6cc / g in a pore diameter range of 20nm to 50nm.
[0110] P8. A catalyst according to any one of paragraphs P1 to P7, wherein the first amorphous silica-alumina has a total pore volume of 0.3cc / g to 2.0cc / g in the pore diameter range of 2nm to 50nm, or a total pore volume of 0.5cc / g to 1.9cc / g in the pore diameter range of 2nm to 50nm, or a total pore volume of 0.7cc / g to 1.8cc / g in the pore diameter range of 2nm to 50nm.
[0111] P9. A catalyst according to any one of paragraphs P1 to P8, wherein the second amorphous silica-alumina has a pore volume of 0.05cc / g to 1.0cc / g in the pore diameter range of 2nm to 6nm, or a pore volume of 0.06cc / g to 0.9cc / g in the pore diameter range of 2nm to 6nm, or a pore volume of 0.07cc / g to 0.8cc / g in the pore diameter range of 2nm to 6nm.
[0112] P10. A catalyst according to any of paragraphs P1 to P9, wherein the second amorphous silica-alumina has a pore volume of 0.05cc / g to 1.0cc / g in the pore diameter range of 6nm to 11nm, or a pore volume of 0.06cc / g to 0.8cc / g in the pore diameter range of 6nm to 11nm, or a pore volume of 0.07cc / g to 0.6cc / g in the pore diameter range of 6nm to 11nm.
[0113] P11. A catalyst according to any of paragraphs P1 to P10, wherein the second amorphous silica-alumina has a pore volume of 0.03 cc / g to 0.18 cc / g in the pore diameter range of 11 nm to 20 nm, or a pore volume of 0.04 cc / g to 0.16 cc / g in the pore diameter range of 11 nm to 20 nm.
[0114] P12. A catalyst according to any of paragraphs P1 to P11, wherein the second amorphous silica-alumina has a pore volume of 0.01cc / g to 0.2cc / g in a pore diameter range of 20nm to 50nm, or a pore volume of 0.015cc / g to 0.15cc / g in a pore diameter range of 20nm to 50nm, or a pore volume of 0.02cc / g to 0.1cc / g in a pore diameter range of 20nm to 50nm.
[0115] P13. A catalyst according to any one of paragraphs P1 to P12, wherein the second amorphous silica-alumina has a total pore volume of 0.3cc / g to 2.0cc / g in the pore diameter range of 2nm to 50nm, or a total pore volume of 0.4cc / g to 1.8cc / g in the pore diameter range of 2nm to 50nm, or a total pore volume of 0.5cc / g to 1.6cc / g in the pore diameter range of 2nm to 50nm.
[0116] P14. A catalyst according to any of paragraphs P1 to P13, wherein the base extrudate has a pore volume of 0.05 cc / g to 0.80 cc / g in the pore diameter range of 2 nm to 6 nm, or a pore volume of 0.08 cc / g to 0.60 cc / g in the pore diameter range of 2 nm to 6 nm, or a pore volume of 0.10 cc / g to 0.50 cc / g in the pore diameter range of 2 nm to 6 nm.
[0117] P15. A catalyst according to any of paragraphs P1 to P14, wherein the base extrudate has a pore volume of 0.05 cc / g to 1.0 cc / g in the pore diameter range of 6 nm to 11 nm, or a pore volume of 0.08 cc / g to 0.90 cc / g in the pore diameter range of 6 nm to 11 nm, or a pore volume of 0.10 cc / g to 0.80 cc / g in the pore diameter range of 6 nm to 11 nm.
[0118] P16. A catalyst according to any of paragraphs P1 to P15, wherein the base extrudate has a pore volume of 0.02 cc / g to 0.3 cc / g in the pore diameter range of 11 nm to 20 nm, or a pore volume of 0.03 cc / g to 0.25 cc / g in the pore diameter range of 11 nm to 20 nm, or a pore volume of 0.04 cc / g to 0.2 cc / g in the pore diameter range of 11 nm to 20 nm.
[0119] P17. A catalyst according to any of paragraphs P1 to P16, wherein the base extrudate has a pore volume of 0.01 cc / g to 0.3 cc / g in the pore diameter range of 20 nm to 50 nm, or a pore volume of 0.012 cc / g to 0.25 cc / g in the pore diameter range of 20 nm to 50 nm, or a pore volume of 0.015 cc / g to 0.2 cc / g in the pore diameter range of 20 nm to 50 nm.
[0120] P18. A catalyst according to any of paragraphs P1 to P17, wherein the base extrudate has a total pore volume of 0.20 cc / g to 1.65 cc / g in the pore diameter range of 2 nm to 50 nm, or a total pore volume of 0.25 cc / g to 1.50 cc / g in the pore diameter range of 2 nm to 50 nm.
[0121] P19. A catalyst according to any of paragraphs P1 to P18, wherein the modifier content is 0.01 wt % to 5.0 wt %, or 0.01 wt % to 2.0 wt %, or 0.1 wt % to 2.0 wt % (based on the total catalyst weight).
[0122] P20. A catalyst according to any one of paragraphs P1 to P19, wherein the catalyst comprises Pt, Pd or a combination of Pt and Pd as a modifier in an amount of 0.01 wt. % to 1.0 wt. %, or 0.3 wt. % to 0.8 wt. % Pt.
[0123] P21. The catalyst of any of paragraphs P1 to P20, wherein the silica content of the first amorphous silica-alumina is in a range of 0.5 wt. % to 15 wt. %, or 1 wt. % to 10 wt. %, or 1.5 wt. % to 8 wt. %.
[0124] P22. The catalyst of any of paragraphs P1 to P21, wherein the silica content of the second amorphous silica-alumina is in a range of 15 wt % to 90 wt %, or 20 wt % to 85 wt %, or 25 wt % to 80 wt %.
[0125] P23. A catalyst according to any one of paragraphs P1 to P22, wherein the ratio of the first amorphous silica-alumina to the second amorphous silica-alumina is in the range of 4:1 to 1:4, or 4:1 to 1:2, or 4:1 to 1:1, or 4:1 to 2:1, or 2:1 to 1:4, or 2:1 to 1:2, or 2:1 to 1:1, 1:2 to 1:1, or 1:4 to 1:2, or 1:4 to 1:1.
[0126] P24. A catalyst according to any one of paragraphs P1 to P23, wherein the catalyst further comprises a matrix material selected from alumina, silica, ceria, titania, tungsten oxide, zirconium oxide, or a combination thereof.
[0127] P25. The catalyst of any of paragraphs P1 to P24, wherein the catalyst comprises 0.01 wt.% to 5.0 wt.% of the modifier, 0 wt.% to 99 wt.% of the matrix material, and 0.1 wt.% to 99 wt.% of the base extrudate.
[0128] P26. A catalyst according to any of paragraphs P1 to P25, wherein the total amount of the first amorphous silica-alumina and the second amorphous silica-alumina in the base extrudate is in the range of 10 wt.% to 95 wt.%, or 20 wt.% to 90 wt.%, or 25 wt.% to 85 wt.%.
[0129] P27. A method for producing a hydrotreated base oil product having an increased aromatic saturation conversion, the method comprising contacting a hydrocarbon feed with a hydrotreating catalyst according to any one of paragraphs P1 to P26 under hydrotreating conditions to produce a base oil product.
[0130] P28. A method according to paragraph P27, wherein the hydrocarbon feed comprises gas oil; vacuum gas oil; long boiling residue; vacuum residue; atmospheric distillate; heavy fuel; oil; waxes and paraffins; used oil; deasphalted residue or crude oil; charge produced by thermal conversion or catalytic conversion processes; shale oil; cycle oil; fats, oils and waxes of animal and vegetable origin; petroleum and slack wax; or a combination thereof.
[0131] P29. A method according to any one of paragraphs P27 to P28, wherein the use of the hydrotreating catalyst as described in any one of claims 1 to 26 increases the aromatic saturation conversion rate compared to the same method performed using a comparative hydrotreating catalyst, the difference between the comparative hydrotreating catalyst is only that the hydrotreating catalyst does not contain both the first amorphous silica-alumina and the second amorphous silica-alumina.
[0132] P30. A method according to paragraph P29, wherein the aromatic saturation conversion rate is increased by at least about 2.0 wt.%, or 5.0 wt.%, or 10 wt.%, or 15 wt.%.
[0133] The present disclosure is not limited to the specific embodiments described in this application, which are intended to illustrate various aspects. Obviously, many modifications and changes can be made without departing from its spirit and scope. In addition to those methods and systems listed here, functionally equivalent methods and systems within the scope of the present disclosure can be apparent from the above representative descriptions. These modifications and changes are intended to fall within the scope of the attached representative claims. The present disclosure is only subject to the terms of the attached representative claims and the full range of equivalents authorized by these representative claims. It will also be understood that the terms used herein are only used for the purpose of describing specific embodiments and are not intended to be limited.
[0134] The foregoing description and its associated embodiments are given for illustrative purposes only. It is not exhaustive and does not limit the invention to the exact form disclosed. Those skilled in the art will appreciate from the foregoing description that modifications and changes may be made according to the above teachings, or modifications and changes may be obtained by practicing the disclosed embodiments. For example, in some cases, the steps described do not need to be performed in the same order discussed or with the same degree of separation. Similarly, various steps may be omitted, repeated or combined as needed to achieve the same or similar purposes. Therefore, the present invention is not limited to the above embodiments, but is defined by the appended claims according to the full scope of their equivalents.
[0135] For purposes of U.S. patent practice, and in other patent offices where permitted, all patents and publications cited in the foregoing description of the invention are incorporated herein by reference to the extent any information they contain is consistent with and / or supplementary to the foregoing disclosure.
Claims
1. A hydroprocessing catalyst for preparing a hydroprocessed dewaxed product comprising a base oil having an improved aromatic saturation conversion rate, wherein the hydroprocessing catalyst comprises A base extrudate comprising a first amorphous silica-alumina (ASA1) and a second amorphous silica-alumina (ASA2), wherein The first amorphous silica-alumina has a pore volume of 0.2 cc / g to 1.0 cc / g in a pore diameter range of 11 nm to 20 nm; The second amorphous silica-alumina has a pore volume of 0.02 cc / g to 0.2 cc / g in a pore diameter range of 11 nm to 20 nm; and The base extrudate has a total pore volume of 0.12 cc / g to 1.80 cc / g in a pore size range of 2 nm to 50 nm; and At least one modifier selected from Groups 6 to 10 and 14 of the periodic table.
2. The catalyst of claim 1, wherein the modifier comprises a metal from Groups 8 to 10 of the Periodic Table.
3. The catalyst of claim 2, wherein the modifier is a Group 10 metal comprising Pt, Pd, or a combination thereof.
4. The catalyst of claim 1, wherein the first amorphous silica-alumina has a pore volume of 0.05 cc / g to 1.0 cc / g in a pore diameter range of 2 nm to 6 nm, or a pore volume of 0.06 cc / g to 0.8 cc / g in a pore diameter range of 2 nm to 6 nm, or a pore volume of 0.07 cc / g to 0.6 cc / g in a pore diameter range of 2 nm to 6 nm.
5. The catalyst of claim 1, wherein the first amorphous silica-alumina has a pore volume of 0.05 cc / g to 1.0 cc / g in a pore diameter range of 6 nm to 11 nm, or a pore volume of 0.06 cc / g to 0.8 cc / g in a pore diameter range of 6 nm to 11 nm, or a pore volume of 0.07 cc / g to 0.6 cc / g in a pore diameter range of 6 nm to 11 nm.
6. The catalyst of claim 1, wherein the first amorphous silica-alumina has a pore volume of 0.24 cc / g to 0.85 cc / g in the pore diameter range of 11 nm to 20 nm, or a pore volume of 0.28 cc / g to 0.7 cc / g in the pore diameter range of 11 nm to 20 nm.
7. The catalyst of claim 1, wherein the first amorphous silica-alumina has a pore volume of 0.05 cc / g to 1.0 cc / g in a pore diameter range of 20 nm to 50 nm, or a pore volume of 0.07 cc / g to 0.8 cc / g in a pore diameter range of 20 nm to 50 nm, or a pore volume of 0.09 cc / g to 0.6 cc / g in a pore diameter range of 20 nm to 50 nm.
8. The catalyst of claim 1, wherein the first amorphous silica-alumina has a total pore volume of 0.3 cc / g to 2.0 cc / g in the pore diameter range of 2 nm to 50 nm, or a total pore volume of 0.5 cc / g to 1.9 cc / g in the pore diameter range of 2 nm to 50 nm, or a total pore volume of 0.7 cc / g to 1.8 cc / g in the pore diameter range of 2 nm to 50 nm.
9. The catalyst of claim 1, wherein the second amorphous silica-alumina has a pore volume of 0.05 cc / g to 1.0 cc / g in the pore diameter range of 2 nm to 6 nm, or a pore volume of 0.06 cc / g to 0.9 cc / g in the pore diameter range of 2 nm to 6 nm, or a pore volume of 0.07 cc / g to 0.8 cc / g in the pore diameter range of 2 nm to 6 nm.
10. The catalyst of claim 1, wherein the second amorphous silica-alumina has a pore volume of 0.05 cc / g to 1.0 cc / g in the pore diameter range of 6 nm to 11 nm, or a pore volume of 0.06 cc / g to 0.8 cc / g in the pore diameter range of 6 nm to 11 nm, or a pore volume of 0.07 cc / g to 0.6 cc / g in the pore diameter range of 6 nm to 11 nm.
11. The catalyst of claim 1, wherein the second amorphous silica-alumina has a pore volume of 0.03 cc / g to 0.18 cc / g in the pore size range of 11 nm to 20 nm, or a pore volume of 0.04 cc / g to 0.16 cc / g in the pore size range of 11 nm to 20 nm.
12. The catalyst of claim 1, wherein the second amorphous silica-alumina has a pore volume of 0.01 cc / g to 0.2 cc / g in a pore diameter range of 20 nm to 50 nm, or a pore volume of 0.015 cc / g to 0.15 cc / g in a pore diameter range of 20 nm to 50 nm, or a pore volume of 0.02 cc / g to 0.1 cc / g in a pore diameter range of 20 nm to 50 nm.
13. The catalyst of claim 1, wherein the second amorphous silica-alumina has a total pore volume of 0.3 cc / g to 2.0 cc / g in the pore diameter range of 2 nm to 50 nm, or a total pore volume of 0.4 cc / g to 1.8 cc / g in the pore diameter range of 2 nm to 50 nm, or a total pore volume of 0.5 cc / g to 1.6 cc / g in the pore diameter range of 2 nm to 50 nm.
14. The catalyst of claim 1, wherein the base extrudate has a pore volume of 0.05 cc / g to 0.80 cc / g in the pore size range of 2 nm to 6 nm, or a pore volume of 0.08 cc / g to 0.60 cc / g in the pore size range of 2 nm to 6 nm, or a pore volume of 0.10 cc / g to 0.50 cc / g in the pore size range of 2 nm to 6 nm.
15. The catalyst of claim 1, wherein the base extrudate has a pore volume of 0.05 cc / g to 1.0 cc / g in the pore size range of 6 nm to 11 nm, or a pore volume of 0.08 cc / g to 0.90 cc / g in the pore size range of 6 nm to 11 nm, or a pore volume of 0.10 cc / g to 0.80 cc / g in the pore size range of 6 nm to 11 nm.
16. The catalyst of claim 1, wherein the base extrudate has a pore volume of 0.02 cc / g to 0.3 cc / g in the pore size range of 11 nm to 20 nm, or a pore volume of 0.03 cc / g to 0.25 cc / g in the pore size range of 11 nm to 20 nm, or a pore volume of 0.04 cc / g to 0.2 cc / g in the pore size range of 11 nm to 20 nm.
17. The catalyst of claim 1, wherein the base extrudate has a pore volume of 0.01 cc / g to 0.3 cc / g in the pore size range of 20 nm to 50 nm, or a pore volume of 0.012 cc / g to 0.25 cc / g in the pore size range of 20 nm to 50 nm, or a pore volume of 0.015 cc / g to 0.2 cc / g in the pore size range of 20 nm to 50 nm.
18. The catalyst of claim 1, wherein the base extrudate has a total pore volume of 0.20 cc / g to 1.65 cc / g in the pore size range of 2 nm to 50 nm, or a total pore volume of 0.25 cc / g to 1.50 cc / g in the pore size range of 2 nm to 50 nm.
19. The catalyst of claim 1, wherein the modifier content is 0.01 wt% to 5.0 wt%, or 0.01 wt% to 2.0 wt%, or 0.1 wt% to 2.0 wt% (based on the total catalyst weight).
20. The catalyst of claim 1, wherein the catalyst comprises Pt, Pd or a combination of Pt and Pd as a modifier in an amount of 0.01 wt% to 1.0 wt%, or 0.3 wt% to 0.8 wt% Pt.
21. The catalyst of claim 1, wherein the silica content of the first amorphous silica-alumina is in a range of 0.5 wt% to 15 wt%, or 1 wt% to 10 wt%, or 1.5 wt% to 8 wt%.
22. The catalyst of claim 1, wherein the silica content of the second amorphous silica-alumina is in a range from 15 wt% to 90 wt%, or from 20 wt% to 85 wt%, or from 25 wt% to 80 wt%.
23. The catalyst of claim 1, wherein the ratio of the first amorphous silica-alumina to the second amorphous silica-alumina is in the range of 4:1 to 1:4, or 4:1 to 1:2, or 4:1 to 1:1, or 4:1 to 2:1, or 2:1 to 1:4, or 2:1 to 1:2, or 2:1 to 1:1, 1:2 to 1:1, or 1:4 to 1:2, or 1:4 to 1:
1.
24. The catalyst of claim 1, wherein the catalyst further comprises a matrix material selected from alumina, silica, ceria, titania, tungsten oxide, zirconia, or combinations thereof.
25. The catalyst of claim 24, wherein the catalyst comprises 0.01 wt% to 5.0 wt% of the modifier, 0 wt% to 99 wt% of the matrix material, and 0.1 wt% to 99 wt% of the base extrudate.
26. The catalyst of claim 1, wherein the total amount of the first amorphous silica-alumina and the second amorphous silica-alumina in the base extrudate is in the range of 10 wt% to 95 wt%, or 20 wt% to 90 wt%, or 25 wt% to 85 wt%.
27. A process for producing a hydrotreated base oil product having increased aromatic saturation conversion, the process comprising contacting a hydrocarbon feed with the hydrotreating catalyst of claim 1 under hydrotreating conditions to produce the base oil product.
28. The process of claim 27, wherein the hydrocarbon feed comprises gas oil; vacuum gas oil; long boiling residue; vacuum residue; atmospheric distillates; heavy fuels; oils; waxes and paraffins; used oils; deasphalted residues or crude oils; charges resulting from thermal or catalytic conversion processes; shale oils; cycle oils; fats, oils and waxes of animal and vegetable origin; petroleum and slack waxes; or combinations thereof.
29. The process of claim 27, wherein use of the hydrotreating catalyst increases the aromatic saturation conversion as compared to the same process performed using a comparative hydrotreating catalyst that differs only in that the hydrotreating catalyst does not contain both the first amorphous silica-alumina and the second amorphous silica-alumina.
30. The process of claim 29, wherein the aromatic saturation conversion is increased by at least about 2.0 wt%, or 5.0 wt%, or 10 wt%, or 15 wt%.
Citation Information
Patent Citations
Noble metal zeolite catalyst for second-stage hydrocracking
US10183282B2
Production of stable lubricating oils by sequential hydrocracking and hydrogenation
US3852207A
Hydrogenation of a hydrocrackate using a hydrofinishing catalyst comprising palladium
US4673487A
Wax isomerization using catalyst of specific pore geometry
US5135638A
Use of modified 5-7 a pore molecular sieves for isomerization of hydrocarbons
US5282958A